Non-acute myocardial infarction-associated cardiogenic shock in Hispanic patients: An analysis from the National Inpatient Sample Database - Nismat Javed; Preeti Jadhav; Sridhar Chilimuri; Johanna Contreras; Jacqueline Tamis-Holland; Jonathan N. Bella (American Heart Journal Plus, 2024)
Background: Current knowledge about non-acute myocardial infarction-associated cardiogenic shock (nAMI-CS) by ethnicity is limited. This study compares clinical features and outcomes of nAMI-CS in Hispanic versus non-Hispanic patients in the U.S. Methods: Hospitalizations with nAMI-CS from 2018 to 2020 were identified using the National Inpatient Sample (NIS) database. Patients were classified by ethnicity (Hispanic vs. non-Hispanic). Statistical analysis, including Chi-square and t-tests, was conducted using STATA version 18. Results: Out of 8607 nAMI-CS hospitalizations, 832 (9.6 %) were Hispanic. Hispanic patients were younger (62.3 ± 15.2 vs. 66.2 ± 15.3 years) and had higher incidences of smoking (2.4 % vs. 2.1 %), coronary artery disease (45.4 % vs. 44.1 %), myocardial infarction (2.9 % vs. 1.9 %), heart failure (10.1 % vs. 9.2 %), and diabetes mellitus (18.9 % vs. 18.1 %). They had lower incidences of hypertension (32.9 % vs. 34.3 %), valve disease (1.9 % vs. 2.1 %), and cerebrovascular disease (6.5 % vs. 8.5 %, all p < 0.005). Hispanic patients had slightly higher in-hospital mortality rates (18.6 % vs. 17 %, p < 0.001), with an adjusted odds ratio (aOR) of 1.20 (95 % CI: 1.01–1.50, p = 0.01). Their hospital stays were longer (17.7 ± 1.87 vs. 13.2 ± 0.31 days, p = 0.03) and costlier ($409,280 ± 591,582 vs. $291,298 ± 461,920, p = 0.03). Conclusion: Hispanic nAMI-CS patients are younger, have more co-morbid conditions, longer hospital stays, higher costs, and higher in-hospital mortality rates than non-Hispanic patients. Further research is needed to understand the mechanisms behind these disparities.